Christian-Muslim encounter in Kerala : a study of the views of Abul Kamal Kaderi - Rasheed, Muhammed Abdul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences , International Islamic University Malaysia, 2018)
This research elaborates and analyses the views of MuÍammad Abul Kamal Kaderi a South Indian scholar of twentieth century Kerala, on Christianity. This attempt is important not least because the Sunni Muslims of Kerala mainly tend to concentrate on the mystical and charismatic features of their scholars. The study looks to fulfill a void of academic studies on the intellectual contributions of traditional Sunni ulama of Kerala particularly in the field of comparative religion. The study, having focussed on Kaderi's two works Naqd al-Anajil (1937) and al-×usam al-Mashhudh, written against the background of an active presence of protestant missionaries in Kerala, has employed a textual analysis of the two books. It also outlines his life, career, intellectual background and contributions, using historical analysis. The study further expounds and assesses his views on Christian theology and distortion of the Bible and discloses his methodology of encountering Christianity. As a result, it is argued that Kaderi's discussion of Christian theology substantially imbibes from the arguments of medieval Muslim apologetic and polemical writings, while his discussion of inauthenticity of the Bible relies upon modern Biblical criticism. Both of his works predominantly follow the polemical method despite containing a minuscule proportion of apologetic arguments, while they also inherently carry an anti-colonial thread. This study further reveals that a key area of Kaderi's intellectual background was constituted by two factors. Firstly, his criticism of certain social customs, which were remarked by hims to have deviated from the Sunnah and justified by some contemporary traditional ulama. Secondly, the disputes that occurred between the traditional Sunni group of ulama and the modernists. Maintaining his capacity as a central executive in Samastha Kerala Jamiyyat al- Ulama one of the most influential ulama organizations of Kerala, Kaderi represented the traditional group of Sunni scholars throughout his life. On the other hand, he often remained a critical insider of the same group, using those arguments, which were incidentally parallel to that of the modernist group of ulama, a fact that led to the marginalisation of his works.